Electoral Education Concept Infusion Into The Nastional Values Curriculum and The Preservation of Democratic Principles in Nigeria - Lawal, Babatunde (Sociology Department, Brawijaya University, 2025)
This article explores integrating Electoral Education into Nigeria's National Values Curriculum to promote democratic principles among youth. It addresses historical challenges in Nigeria's democracy, advocating for educational intervention to counter electoral malpractices and voter apathy. Efforts by IFES and NERDC to incorporate Electoral Education are examined, mapping themes on democracy, elections, governance, and citizenship. The curriculum aims to inform citizens and encourage responsible participation. Core democratic principles, such as equality, dignity, transparency, and participation, underpin the curriculum. It highlights the importance of teacher training and professional development and concludes that successful curriculum integration empowers students to understand, engage in, and uphold democratic processes for the nation's future.